Match activity of players in selected positions in UEFA youth league and U19 Slovak first division - Nemec, M.; Kollar, R.; Pivovarnicek, P.; Stefanik, D. (Sport Science - International Scientific Journal of Kinesiology, 2019)
The aim of the study was to quantify and compare selected indicators of players' match activity (n = 24) in the UEFA Youth League (UEFAYL) and in the U19 Slovak First Division (1. LSDS). The playing positions of the players were as follows: central defender (CD), central midfielder (CM), and forwards (F). The study focused on assessment and comparison of the selected indicators of match activity: the number of successful match activities (HCJ+), the number of unsuccessful match activities (HCJ-), the total number of the match activities (HCJsum), the percentage of the successful match activities (SUC); the points awarded (Points) and the quality category of a player (Cat). Regarding all indicators, the statistical analysis showed no significant differences in the match activity between the players in the UEFAYL and in the 1. LSDS.